Perceptions of Men on Male Partners Involvement in Maternal and Child Health: An Analysis of Kuria East SubCounty, Migori County, Kenya - Maureen Kwamboka Nyabuto; Taji Isindu Shivachi; John Odero Sibuor; Wilson A.P. Otengah (Pan-African Journal of Health and Environmental Science)
Background: Male partner involvement is critical to maternal and child health outcomes. In Kenya, male partners are entitled to a two-week paternal leave with full pay to encourage male partner support in antenatal and postpartum care services, breastfeeding, complementary feeding, and health education. However, the involvement of males in maternal and child health remains inadequate. This could be attributed to several factors. Consequently, this study investigated perceptions of men on male partner involvement in maternal and child health in Kuria East Sub-County, Migori County, Kenya